Adaptive PHY-MAC design for broadband wireless systems - Prasad, Ramjee (River Publishers series in communications, 2010)
This book will answer questions such as, how individual techniques relate to each other, how can we benefit the gains by suitable combinations of different technologies and how to choose different technological solutions in different scenarios, etc.